Clinical and etiological spectrum of prolonged fever and special reference to HIV patients at a tertiary care centre - Behera, Suresh; Subrahmanyam, D. K. S.; Bajpai, Jyoti; Pradhan, Akshyaya; Singh, Abhishek (International Journal of Research in Medical Sciences, 2018)
Background: Prolonged fever is a diagnostic challenge and will tend to remain so in times to come because of the changing spectrum of etiologies and influence of technology, environmental changes, and many other ill-understood factors which influence the etiological spectrum. Prolonged fever is also undergoing change in its duration. The aim of the present was study to determine the etiologies of prolonged fever in patients in India and to evaluate the clinical and etiological relationship between the diagnosis and patient’s laboratory data. Methods: Patients aged more 13 years with fever >38.3ºC for more than three weeks without apparent source after preliminary investigations were included prospectively over a period of twenty two months. Fever duration, symptom, signs, laboratory investigations and final diagnosis were recorded. The distribution of etiologies and age, fever duration, laboratory examinations, and associated symptoms and signs were analyzed. Results: Out of total of 86 patients were enrolled, fifty one (59.3%) were men. The median age was 28 years (range, 13-65 yr). Among 86 patients, diagnosis could be made in only 69 (80.2%) patients. Infections, neoplasms, NIIDs, miscellaneous causes were responsible for prolonged fever in 42 (48.8%), 18 (20.9%), 6 (7%), and 3 (3.5%) patients respectively. Seveteen (19.8%) cases remained undiagnosed, even after relevant investigations, six of them recovered spontaneously. Tuberculosis (TB) was the cause of prolonged fever in 21 (24.4%) patients. Conclusions: Infections, amongst which tuberculosis, remain the major cause of prolonged fever and its subset: fever of unknown origin (FUO), in this country. The percent of undiagnosed cases appears to be identical worldwide.